Dynamic Load Balancing with Multipath Routing in Software Defined Networking - Neupane, Bijay; Pudashine, Kumar (Journal of Science and Technology, 2026)
Traditional Ethernet networks were limited to routing schemes. A single best path was used by the Spanning Tree Protocol (STP). This was a major cause for the limitation in the throughput and the increased network latency. Multipath routing scheme is one of the solutions where multiple paths available in the network are used for traffic forwarding. If the load is being forwarded to the multiple paths, load balancing finds its application to balance the load among different paths. In this paper, a multipath routing scheme is proposed along with the load balancing among the available multiple paths in Software Defined Networking (SDN) environment. SDN is an emerging networking paradigm where control plane is separated from the data plane. Mininet is used as the network simulation tool along with the Ryu controller to support network programmability feature on the control plane.